Family Support And The Emotional Response Of Diabetes Mellitus Patients In The Internal Medicine Specialist Clinic At Delta Surya Hospital, Sidoarjo - Anik Nuridayanti; Achmad Parjiko Adji Sanjaya; Suhartini Suhartini; Khoirudin Khoirudin (Jurnal Pendidikan dan Konseling (JPDK), 2020)
Diabetes mellitus has psychological impacts such as stress or anxiety, so that they need their families' supports to make the patients' emotional responses good. The objective of this research was to know the relationship between the families' supports and the diabetes mellitus patients' emotional responses in Internal Diseases Clinics Chamber of Delta Surya Sidoarjo Hospital Sidoarjo City. The design of this research was correlational analytics with a cross-sectional approach. The population was 304 diabetes mellitus patients, and 61 respondents were taken as samples by accidental sampling technique. The independent variable was the families' supports and the dependent one was the diabetes mellitus patients' emotional responses. The independent and dependent variable data were obtained from questionnaires, and analyzed with Spearman Rank Test with Mean value p < 0.05. The research results were 33 respondents (54.1%) had good families' supports, and 37 respondents (60.7%) had good emotional responses. There was a relationship between the families' supports and the diabetes mellitus patients' emotional responses (Spearman Rank, p value = 0.000 < ? 0.05). The relation level was high and positive (Correlation Coefficient: 0.610). The conclusion was there was a relationship between the families' supports and the diabetes mellitus patients' emotional responses, where the better the families' supports the better the patients' emotional responses. The research recommends that family members maintain and continue to give full support to patients.